2020
DOI: 10.1097/aud.0000000000000945
|View full text |Cite
|
Sign up to set email alerts
|

The Virtual Reality Lab: Realization and Application of Virtual Sound Environments

Abstract: To assess perception with and performance of modern and future hearing devices with advanced adaptive signal processing capabilities, novel evaluation methods are required that go beyond already established methods. These novel methods will simulate to a certain extent the complexity and variability of acoustic conditions and acoustic communication styles in real life. This article discusses the current state and the perspectives of virtual reality technology use in the lab for designing complex audiovisual co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Many research groups have focused on creating realistic acoustical setups in the laboratory 20,21 and to include visual cues. [22][23][24][25] Fewer research groups 23,26,27 have focused on the behavioral tasks performed during a laboratory study. Often, traditional speech recall tests are used, where test participants listen and repeat prerecorded words or sentences.…”
Section: Introductionmentioning
confidence: 99%
“…Many research groups have focused on creating realistic acoustical setups in the laboratory 20,21 and to include visual cues. [22][23][24][25] Fewer research groups 23,26,27 have focused on the behavioral tasks performed during a laboratory study. Often, traditional speech recall tests are used, where test participants listen and repeat prerecorded words or sentences.…”
Section: Introductionmentioning
confidence: 99%
“…The data of ILDs (Fig. 5) show an expected increasing pattern with laterality for Scene 1, the positions spanning radially (13)(14)(15)(16)(17) show only a subtle change of ILD possibly due to early reflections. We see only a small difference between the HP and the LS and only for a few positions (5,10,11), which could be related to Ambisonics reproduction artifacts at high frequencies with LS reproduction.…”
Section: Resultsmentioning
confidence: 86%
“…5. Interaural level differences for different positions in Scene 1 (source positions 1-12) and Scene 2 (source positions [13][14][15][16][17]. Solid lines show the data for reverberant space using the recorded baseline (HP) and the modelled loudspeaker auralization (LS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Völk argued for the use of virtual acoustic methods in psychoacoustics and auditory studies because of their relatively simple application (Völk, 2013). Hohmann discussed the current state and the perspectives of virtual reality technology used in the lab for designing complex audiovisual communication environments for hearing assessment and hearing device design and evaluation, the result showed that the virtual reality lab in its current state marks a step toward more ecological validity in labbased hearing and hearing device research (Hohmann et al, 2020). Ahrens investigated source localization accuracy with the head mounted displays (HMD) in virtual reality providing a varying amount of visual information, which showed that the lateral localization error induced by wearing HMD was due to alterations of HRTF (Ahrens et al, 2019).…”
Section: Introductionmentioning
confidence: 99%